Green Economy Initiatives for Sustainable Agriculture in Kenyan Universities: A Case Study of Meru University - Njoka, Moses; Richard Kirigiah; Kemboi, VIctor (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
This study investigated the integration of green economy initiatives aimed at fostering sustainable agriculture within Kenyan universities, with a specific focus on Meru University as a case study. The research examined the strategies, programs, and educational practices implemented by Meru University to promote sustainable agricultural practices in line with green economy principles. Utilizing a combination of literature review, interviews, and analysis of institutional policies and curriculum, the study evaluated the effectiveness and challenges associated with these initiatives. Key findings revealed successful pedagogical approaches, including the incorporation of sustainable farming techniques, the promotion of renewable energy use, and the integration of eco-conscious principles into the curriculum. Additionally, the study identified barriers to implementation, such as resource constraints and institutional inertia. Insights from Meru University’s experience provides valuable lessons for policymakers, educators, and stakeholders interested in advancing green economy initiatives and enhancing sustainable agricultural education within the higher education sector in Kenya and beyond.